New findings in osteoarthritis pathogenesis: therapeutic implications. (January 2013) - Pulsatelli, Lia; Addimanda, Olga; Brusi, Veronica; Pavloska, Branka; Meliconi, Riccardo
This review focuses on the new perspectives which can provide insight into the crucial pathways that drive cartilage-bone physiopathology. In particular, we discuss the critical signaling and effector molecules that can activate cellular and molecular processes in both cartilage and bone cells and which may be relevant in cross talk among joint compartments: growth factors (bone morphogenetic proteins and transforming growth factor), hypoxia-related factors, cell–matrix interactions [discoidin domain receptor 2 (DDR2) and syndecan 4], signaling molecules [WNT, Hedgehog (Hh)]. With the continuous progression of our knowledge on the molecular pathways involved in cartilage and bone changes in osteoarthritis (OA), an increasing number of potentially effective candidates for OA therapy are already under scrutiny in clinical trials to ascertain their possible safe use in an attempt to identify molecules active in slowing or halting OA progression and reducing joint pain. We then review the principal molecules currently under clinical investigation.